Myokine/Adipokine Response to “Aerobic” Exercise: Is It Just a Matter of Exercise Load? - He, Zihong; Tian, Ye; Valenzuela, Pedro L.; Huang, Chuanye; Zhao, Jiexiu; Hong, Ping; He, Zilin; Yin, Shuhui; Lucia, Alejandro (Frontiers in Physiology, 2019)
Purpose: Exercise health benefits are partly mediated by exertional changes in several myokines/adipokines. but little is known on individual variability, which is an important question in the context of personalized exercise prescription. This study aimed to compare the acute response of some of these biomarkers to aerobic exercise performed at the intensity corresponding to the maximum fat oxidation rate (FATmax) or the ‘anaerobic’ threshold (AT). Methods: Following a cross-over, counterbalanced design, 14 healthy untrained men (23±1 years) performed a 45-minute exercise bout at their FATmax or AT intensity (been previously determined through incremental exercise tests). The concentration of interleukin (IL)-15, follistatin, myostatin, fibroblast-growth factor (FGF)-21, irisin, resistin and omentin was measured at baseline and 0, 1, 3, 24, 48 and 72 hours post-exercise. Results: AT exercise was performed at a higher intensity (85±8 vs 52±14% of maximal oxygen uptake [VO2max], p<0.001) and induced a higher energy expenditure (p<0.001) than FATmax, whereas a greater fat oxidation was observed in the latter (p<0.001). A higher peak response of FGF-21 (+90%, p<0.01) and follistatin (+49%, p<0.05) was found after AT-exercise, as well as a trend towards a higher peak level of omentin (+13%, p=0.071) and a greater decrease in resistin (-16%, p=0.073). AT induced a greater omentin response immediately after exercise that FATmax (p=0.020), but no consistent differences were observed between conditions for the rest of variables or for the proportion of individual responders (p>0.05). Conclusion: In summary, Iincreasing exercise intensity load (from FATmax to AT) maximizes results in a higher response of the FGF-21, follistatin and omentin response to aerobic exercise, with the subsequent potential cardiometabolic benefits. No intensity effects were, however, observed on the remainder of biomarkers. or on the rate of responsiveness. Future research should address if manipulating other exercise variables (e.g., type, frequency) can promote a higher myokine/adipokine individual responsivenessresponse.